2015
DOI: 10.1021/ac503964j
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Microfluidic Capillary Electrophoresis-Electrospray Ionization Devices with Online MS Detection for the Separation and Characterization of Intact Monoclonal Antibody Variants

Abstract: Here, we demonstrate an integrated microfluidic capillary electrophoresis-electrospray ionization (CE-ESI) device for the separation of intact monoclonal antibody charge variants with online mass spectrometric (MS) identification. The need for dynamic coating and zwitterionic background electrolyte (BGE) additives has been eliminated by utilizing surface chemistry within the device channels to control analyte adsorption and electroosmotic flow (EOF) while maintaining separation efficiency. The effectiveness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
111
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(113 citation statements)
references
References 46 publications
2
111
0
Order By: Relevance
“…41,42 Gahoual and co-workers demonstrated that particular glycopeptides having a difference of one galactose could be baseline separated 13 whereas Redman et al did not observe mobility shifts between intact mAb glycoforms due to the low impact of 162 Da on the mass of intact mAb (≈0.1%). 28 Our work demonstrated that, concerning glycoform with a difference of one galactose residue, the middle-up approach does not allow one to observe baseline separations. The mass of galactose moiety accounts for ≈0.6% of the Fc/2 domain and ≈0.2% of the F(ab′) 2 domain.…”
Section: Cze/collection Fractionmentioning
confidence: 83%
“…41,42 Gahoual and co-workers demonstrated that particular glycopeptides having a difference of one galactose could be baseline separated 13 whereas Redman et al did not observe mobility shifts between intact mAb glycoforms due to the low impact of 162 Da on the mass of intact mAb (≈0.1%). 28 Our work demonstrated that, concerning glycoform with a difference of one galactose residue, the middle-up approach does not allow one to observe baseline separations. The mass of galactose moiety accounts for ≈0.6% of the Fc/2 domain and ≈0.2% of the F(ab′) 2 domain.…”
Section: Cze/collection Fractionmentioning
confidence: 83%
“…One example involves commercial microchips sold through 908 Devices (Boston, MA). A number of publications involving this interface have been reported [71][72][73]. A distinct advantage of such systems includes administration of capillary coating in the gas phase through chemical vapor deposition [71].…”
Section: Capillary Zone Electrophoresis In Microfluidic Chipsmentioning
confidence: 99%
“…Ramsey et al used the MCE-MS device described in [85], for the separation and characterization of charge variants of intact monoclonal antibodies (Infliximab) [87].…”
Section: Mce-ms Devices With Integrated Sprayermentioning
confidence: 99%